ANESTHESIOLOGICAL PROTECTION OF NEWBORNS DURING CESAREAN SECTION IN WOMEN WITH SEVERE MITRAL STENOSIS - Muminov Abdukhalim Abduvakil; Matlubov Mansur Muratovich (Scholar Express Journals, 2023)
The results of study of 38 preterm infants (19 patients in each group) have been presented. The aim of the research was a comparative assessment of the condition of newborns extracted by CS from mothers with clearly marked mitral stenosis (MS) against the background of the use of the traditional variantof GMA with ALV (artificial lung ventilation) and balanced combined general anesthesia based on EB with reduced concentrations of local anesthetics.It was found that MCA with ALV against the background of epidural block has a less marked negative effect on newborns in comparison with GMA with ALV makes it possible to preserve the adaptive capacity of the child to a greater extent during the period of early adaptation to extrauterine conditions, despite the extremely unfavorable initial background (prematurity; DBC, significant decrease in maternal coronary reserves due to clearly marked MS (1.9-1, 1 cm2 ).
Keywords: condition; newborns caesarean; severe mitral stenosis